The Effect of Mirtazapine on Reducing Chronic Stress in Male Rats: Mirtazapine for Reducing Chronic Stress in Rats - Barbar Shemirani, Samira; Nasiri Khalili, Mohammad Ali; Mahdavi, Seyed Mohammad; Modarresi Chahardehi, Amir (International Clinical Neuroscience Journal, 2022)
Background: Mirtazapine (Mtz) has attracted attention for its anti-anxiety properties. We aimed to explore the impacts of chronic unpredictable stress (CUS) using Mtz treatment as a post-traumatic stress disorder (PTSD) drug and to determine body weight and plasma corticosterone levels at various times in rats. Methods: Adult male Wistar rats were administered nine days of CUS in this research and then received Mtz after CUS or when the CUS began. At the end of the CUS protocol, the rats were subjected to the elevated plus maze (EPM) test and open-field test (OFT) (for anxiety-like behavior) followed by the forced swimming test (FST) and tail suspension test (TST) (for depression behavior). The CUS protocol included body weight measurement, a sucrose preference test (SPT), and plasma corticosterone (CORT) levels. Results: Significantly decreased body weight and increased plasma CORT levels were seen in the CUS group. Mtz at 10 mg/kg significantly increased body weight in rats after being exposed to CUS, demonstrating anti-anxiety activity. The process was discovered to be linked with a decline in plasma CORT and no significant difference was seen with respect to body weight compared with the control group, as we found in one of the treated groups (Mtz after CUS). Conclusion: A decrease in CORT levels in serum plasma and modulated body weight might be a key mechanism by which Mtz exerts its therapeutic potential as an antidepressant, and it would be safe to take orally after stressful conditions.